Acute carbon monoxide toxicity in a paediatric cohort: analysis of 10 boys poisoned during a scuba diving lesson. (2nd September 2018) - McDermott, John Henry; Reynard, Charles; Perry, Jonathan; Dear, James W.; Child, Fran; Jenner, Rachel
Abstract: Background: Recent public health strategies have contributed towards a significant reduction in the incidence of carbon monoxide (CO) poisonings. When events do occur, symptoms can vary dramatically depending on the carboxyhaemoglobin level and individual factors. Most reports to date focus on individual cases or larger retrospective reviews of diverse cohorts. There are very few reports of CO exposure related to scuba diving activities. Methods: We describe the clinical sequelae experienced by 10 children who were exposed to CO during a scuba diving lesson. We collate patient data in the context of a severely affected individual and employ exponential decay calculations to estimate half-life. Results: Six of the patients exposed to CO were symptomatic. The most severely affected individual suffered multi-organ effects, including myocardial damage, and required intensive care unit admission. The remaining cohort demonstrated notable clinical variability. The half-life of carboxyhaemoglobin on high flow oxygen in this cohort was ∼75 min, in line with previous estimates. Conclusion: This work described an uncommon clinical presentation, representing the largest single cohort of its kind. This work exemplifies the variable symptomatology of CO toxicity, of which clinicians should be alert to if patients fall ill after scuba diving.